(untitled) (Cadernos de Sociomuseologia, 2023)
In Brazil, the institutionalization of the Museology field took place through the creation of Courses in the area – one in the Northeastern region, at Federal University of Bahia/UFBA and two in the Southeastern region, at Federal University of the State of Rio de Janeiro/UNIRIO and at Free School of Sociology Foundation of São Paulo/Fesp. This field, composed of disputing agents, will be investigated in this article through sociological analysis in order to, understanding how It works, congruently investigate the uses of the tools used by its agents between the decades of 1960 and 1980. Understanding the particular form this logic takes becomes especially necessary in the perception of the Brazilian Museology field formation, as an analytical category, since it is important to consider the symbolic power relations existent in this space during its formation. Professionals linked to each of the Schools problematized and developed, through specific epistemological statutes, practices and theoretical conceptions conveyed to technical museum work, as well as to Museology, and such perspectives reverberate in the field to this day. Keywords: Scientific field. Museology in Brazil. Colonialism. Museology courses